The Group Potency in Audit Teams and its Impact on the Accounting Related Task Performance (Global Journal of Management and Business Research, 2014)
The present study tests the impact of group potency on the auditors' accounting related task performance, by determining the impacts of the drivers affecting the development of group potency in audit teams, for the purpose of making up the deficiency in question. In consequence of the analysis of audit groups constituted of 160 independent auditors from 39 audit firms, through a longitudinal experiment, it was determined that, as a result of the development of the team's group potency, the audit performance is positively affected. Besides, collaboration between team members, previous experiences of group members, group identification of individuals and goal clarity were determined as factors contributing to the development of group potency within the audit team. On the other hand, no relationship could be established between group autonomy and group potency. As for accountability and group side variables, these were determined as factors having an impact in the structural model.
Keywords: group potency; task performance; group identification; collaboration; goal clarity